Vatican II and the American Press: Conflict to Transparency - Gribble, Richard (The catholic historical review, 2019)
Vatican II was a milestone in providing access to the world press of the day-to-day activities of the Council Fathers. During the first period (1962) journalists were generally frustrated in their ability to report the Council's daily events, but this improved greatly in the three remaining periods, due in large measure to a more open style of Pope Paul VI, a vastly improved Vatican Press Office, and the work of the United States Catholic Bishops Press Panel. While some frustration remained, the world press experienced a more transparent Church.